THE IMPLEMENTATION OF INFOGRAPHICS IN SPEAKING FOR SOCIAL INTERACTION COURSE - Bimantara, Ketut Lingga; Myartawan, I Putu Ngurah Wage; Dewi, Kadek Sintya (International Journal of Language and Literature, 2020)
This study aimed to observe the implementation of infographics in speaking for social interaction course and analyze students' responses toward infographics implementation.Â  This study used an embedded mixed-method design with qualitative dominant in which the primary component is qualitative and the supporting component is quantitative. This study was conducted in English Language Education Department of Ganesha University especially in speaking for social interaction course. The results showed that in implementing infographics in the speaking class, the lecturer used infographics in pre-activity, whilst-activity, post-activity. The researcher found the use of infographics only once in pre-activity as brainstorming media, twice in whilst activity as the practice for students to know the capability of the students' speaking skill, and the rest of the meetings the lecturer used the infographics in post-activity as evaluation. Additionally, the implementation of infographics in post-activity also got positive responses from most of the students.Â  Majority of the students stated that the use of infographics was very beneficial in supporting students to speak better.